Pelatihan Simulasi Perakitan Komputer Menggunakan Cisco IT Essenstials Virtual, Desktop Pada Siswa SMK Muhammadiyah Parakan, Tangerang Selatan - Tedi Purwanto; Simon Simarmata; Jamaludin (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The development of computer technology is very fast, almost all technology components use it. The use of technology has inseparable parts that are closely related to each other such as hardware, software and users (brainware). Computer technology for hardware develops fast and is accompanied by the development of applications or software that is so fast too. The role of the computer is to facilitate communication, entertainment facilities, work and business support as well as the efficiency of the learning process. So that today's technological developments society is required to adapt to the more frequent we interact using computers so that we find some problems in operating. This is what prompted us Lecturers from Pamulang University Informatics Engineering Study Program to try to share knowledge and experience with students of the Muhammadiyah Parakan Vocational School, South Tangerang, how to get to know computers in terms of hardware by knowing what devices are on the computer. The presence of this training is to improve the quality and knowledge of students to know more about computer equipment. With this training, it is hoped that it will be able to open students' insights into the importance of computer technology and know which hardware parts or parts must be replaced and the steps if a problem occurs. . The service carried out by the Faculty of Engineering Informatics Engineering Study Program, University of Pamulang with the title "COMPUTER ASSEMBLY SIMULATION TRAINING USING CISCO IT ESSENTIALS VIRTUALDESKTOP FOR STUDENTS OF SMK MUHAMMADIYAH PARAKAN, TANGERANG SELATAN," with the initial stage being the installation of an application that will be carried out by a team of lecturers from Informatics Engineering Pamulang University which carries out service to the Muhammadiyah Parakan Vocational School, the next step is to conduct training for students of the Parakan Muhammadiyah Vocational School. The team of presenters will theoretically present training materials with students as objects or listeners and executors. Then after the theory session will be followed by a practical session